Perceived enablers of exclusive breastfeeding by teenage mothers in Ghana - Angela K. Acheampong; Makombo Ganga-Limando; Lydia Aziato (South African Family Practice)
Background: Exclusive breastfeeding for the first 6 months can prevent diseases, boost immunity and improve quality of lives of infants. Ghana implemented programmes aimed at reaching the global target of increasing exclusive breastfeeding for the first 6 months to at least 50% by the year 2025. The country witnessed a decline in the overall rate of exclusive breastfeeding and an increase in the number of teenage mothers. Globally, teenage mothers are less likely to breastfeed than mothers of other age groups. Understanding enablers of exclusive breastfeeding by teenage mothers is important for any intervention aimed at improving exclusive breastfeeding rates and the quality of lives of infants.